Taqyīm Ta‘līm al-Lugah al-‘Arabiyyah bi Ṭarīqah al-Ikhtibār fī Māddat al-Adab al-‘Arabī - Ulfi Usykuriyah Khoiry (JICALLS: Journal of Arabic Education, Linguistics, and Literature Studies, 2026)
The students' understanding of the lesson is a sign of the success of education, and one way to determine the success of students after the learning process is to evaluate the test. The test has specific goals and conditions with special rules. The use of tests in Arabic literature is different from other language tests because the process of literature in teaching Arabic is connected to the taste of language. It is clear that the method of this research is library research with data sources related to tests in literature. This research takes primary data from the book "Types of Tests in Literature" by Muhammad Ali Al-Khouli and other books, as well as using various publications to stimulate analysis in this study. Data analysis in this study is descriptive. The results of the research indicate that the evaluation of Arabic language teaching through tests in Arabic literature is objective and subjective, and tests in literature can include 3 aspects: knowledge, understanding, and expression.